535The epidemiology of all-cause and cause-specific mortality following release from prison in 11 countries. (2nd September 2021) - Borschmann, Rohan; Tibble, Holly; Spittal, Matthew; Preen, David; Pirkis, Jane; Larney, Sarah; Rosen, David; Young, Jesse; Kinner, Stuart
Abstract: Background: More than 30 million adults are released from incarceration globally each year. Many experience complex physical and mental health problems, and are at markedly increased risk of preventable mortality. Despite this, evidence regarding the global epidemiology of mortality following release from incarceration is insufficient to inform the development of targeted, evidence-based responses. Many previous studies have suffered from inadequate power and poor precision, and even large studies have limited capacity to disaggregate data by specific causes of death, sub-populations or time since release to answer questions of clinical and public health relevance. Methods: We aimed to comprehensively document the incidence, timing, causes and risk factors for mortality in adults released from incarceration. We created the Mortality After Release from Incarceration Consortium (MARIC), a multi-disciplinary collaboration representing 29 cohorts of adults who have experienced incarceration from 11 countries. Findings across cohorts will be analysed using a two-step, individual participant data meta-analysis methodology. Results: Using linked data from the 29 individual cohorts, the combined sample includes 1, 337, 993 individuals (89% male), with 75, 795 deaths recorded over 9, 191, 393 person-years of follow-up. Preliminary analyses indicate a marked elevation in mortality risk following release from incarceration, with this risk beginning on the day of release. At the time of writing, more detailed analyses are underway regarding all-cause and cause-specific deaths – along with risk and protective factors – and findings will be presented at the WCE conference. Conclusions: The MARIC consortium represents an important advancement in the field, bringing international attention to this problem. Key messages: The MARIC consortium will provide internationally relevant evidence to guide policymakers and clinicians in reducing preventable deaths in this marginalised population.